2014
DOI: 10.1037/scp0000039
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing near-death experiences to professional healthcare providers and nonprofessionals.

Abstract: Researchers examined 88 near-death experiencers' (NDErs') perceptions of 188 of their most noteworthy experiences disclosing their near-death experiences (NDEs) to professional healthcare providers-medical, mental, social, and spiritual/religious. Participants scored 7 or higher on the NDE Scale and were 72% female and 28% male; aged 21 to 81 years, mean age 56; 89% Caucasian, 3% Native American, 1% Black, 1% Hispanic, and 6% mixed or other; and 18% Protestant, 6% Roman Catholic, 2% Jewish, 1% Buddhist, 51% sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…She found that potentially helpful or harmful healthcare professionals' (HPs') responses to clients'/patients' disclosures of NDEs seemed to reflect one or more of four factors: (a) label, whether or not, when clients/patients disclosed NDEs to an HP, the HP recognized and labeled the experiences as NDEs; (b) spiritual, whether the HP considered NDEs to be actually or potentially spiritually benevolent or malevolent; (c) diagnosis, whether the HP considered NDEs to be unrelated to or an indication of mental disorder; and (d) real, whether or not the HP considered NDEs might be objectively real rather than imaginary or hallucinatory. These factors were subsequently verified by NDErs themselves as differentiating whether they felt helped or harmed by the way they perceived HPs to have responded to their disclosures of their NDEs (Holden, Kinsey, & Moore, 2014;Holden, Kinsey, Henson, & Greyson, 2016).…”
Section: Creation Of Initial Instrumentmentioning
confidence: 92%
See 1 more Smart Citation
“…She found that potentially helpful or harmful healthcare professionals' (HPs') responses to clients'/patients' disclosures of NDEs seemed to reflect one or more of four factors: (a) label, whether or not, when clients/patients disclosed NDEs to an HP, the HP recognized and labeled the experiences as NDEs; (b) spiritual, whether the HP considered NDEs to be actually or potentially spiritually benevolent or malevolent; (c) diagnosis, whether the HP considered NDEs to be unrelated to or an indication of mental disorder; and (d) real, whether or not the HP considered NDEs might be objectively real rather than imaginary or hallucinatory. These factors were subsequently verified by NDErs themselves as differentiating whether they felt helped or harmed by the way they perceived HPs to have responded to their disclosures of their NDEs (Holden, Kinsey, & Moore, 2014;Holden, Kinsey, Henson, & Greyson, 2016).…”
Section: Creation Of Initial Instrumentmentioning
confidence: 92%
“…They typically report that integrating these aftereffects into their subsequent lives is a difficult and isolating process (Furn, 1987;Holden 2012;Noyes et al, 2009). These challenges are exacerbated when they disclose their NDEs to confidants who respond with uncertainty, doubt, or even cynicism (Brumm, 2006;Holden, Kinsey, & Moore, 2014).…”
mentioning
confidence: 99%
“…In order to be helpful to NDErs who report environmental effects, HPs themselves need to be well educated about these phenomena. We echo the call for these topics to be addressed in HPs' initial professional preparation and their continuing education (Foster, James, & Holden, 2009;Holden, Kinsey, & Moore, 2014).…”
Section: Implications For Healthcare Professionals Working With Ndersmentioning
confidence: 95%
“…The findings reported above carry implications for healthcare professionals (HPs) whose patients and clients include NDErs. In general, NDErs have reported both helpful and harmful experiences disclosing their NDEs to HPs-medical, such as nurses and physicians; mental, such as counselors and psychologists; social, such as social workers; and religious/spiritual, such as chaplains and pastors (Holden, Kinsey, & Moore, 2014). Holden et al (2014) found that harmful disclosure experiences involved the HP responding to NDE disclosure by failing to recognize the experience as an NDE, by failing to acknowledge its reality or potential reality, by pathologizing the NDE or NDEr based on the NDE alone, and/or by demonizing the experience or experiencer.…”
Section: Implications For Healthcare Professionals Working With Ndersmentioning
confidence: 99%
See 1 more Smart Citation